Treasury Single Account as a Driver of Sustainability for Public Expenditure in Nigeria: Array - Babatunde, Dorcas Adebola; Olanike, Oshatimi Omowumi; Oladunmomi, Omilegan Paul (The Journal of Accounting and Management, 2021)
The research work examined the impact of treasury single account on public expenditure in Nigeria. The objective of the study was to examine how Federal Government Deposit affects Total Capital Expenditure (TCE), Total Recurrent Expenditure (TRE), Total Federally Collection Revenue (TFCR), Total Public Borrowing (TPB) in Nigeria. This Study is predicated on the Musgrave and Rostow theory of public expenditure. Secondary data source was explored in presenting the facts of the situation. The secondary data were obtained from relevant literatures, Central Bank of Nigeria Statistical Bulletin and National Bureau of Statistics publications among other. Data were tested using the Ordinary Least Square Linear Regression model. From the Central Bank of Nigeria Statistical Bulletin and National Bureau of Statistics, information concerning Federal Government Deposit, Total Capital Expenditure, Total Recurrent Expenditure, Total Federally Collection Revenue, Total Public Borrowing in Nigeria were extracted. The findings show that all the coefficients of the explanatory variables in the models are all statistically significant to Federal Government Deposit (FGD) except public borrowing. The study concluded that, government borrowing is a devil that government must live with in other to enhance investment, social and economic development of the country. The study then recommends among others, that to ensure sustainable in treasury single account, all funds mobilized and disbursed to all tiers of government must be sufficient, efficiently and judiciously utilized and prudent with their spending. The government should pay attention and do everything possible to prevent mismanagement of funds and income leakages in all MDAs